The Effect Of Democratic Leadership On Employee Performance At The Marioriaja Village Office - Verri Ginoga; Ervina Ervina; Lutfia Fuji Awalya; Ibrahim Ibrahim (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Lamappapoleonro, 2026)
This study aims to analyze the effect of democratic leadership style on employee performance at the Marioriaja Village Office, Marioriwawo District, Soppeng Regency. Democratic leadership is viewed as an approach that can create a participatory and open work environment while encouraging employee involvement in decision-making processes. The research employs an associative quantitative approach using a survey method. The population consists of 18 employees, all of whom were selected as the sample through a saturated sampling technique. Data were collected using a Likert-scale questionnaire and analyzed through simple linear regression. The results indicate that democratic leadership style has a positive and significant effect on employee performance, as reflected by the regression equation Y = 9.68 + 0.608X and a significance value of 0.007. These findings demonstrate that the better the implementation of leadership that values employee opinions and promotes cooperation, the higher the level of productivity and the quality of public services within the village government